Analisis Fluktuasi Total Electron Content (TEC) Akibat Gempa Palu dengan Formosat-3 / COSMIC - Sari, Atika; Cahyadi, Mokhamad Nur (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Earthquakes are vibrations that occur as a result of plate shifts. When an earthquake occurs, it will cause three kinds of waves, and one of them is an acoustic wave that moves vertically and affects electrons that move freely in the ionosphere. This study aims to analyze Total Electron Content (TEC) fluctuations due to earthquakes using FORMOSAT-3 / COSMIC data. The method used is the analysis of the time and location of the occurrence of TEC fluctuations from the results of plotting the FORMOSAT-3 / COSMIC data against the time and location of the earthquake. The data used is netCDF data, which contains information on the TEC value and occultation time which on FORMOSAT-3 / COSMIC, the data was taken using the Global Positioning System Radio Occultation (GPSRO) technique. The results of the Palu earthquake on September 28, 2018 obtained 28 occultations with an anomaly time of 10 minutes after the earthquake and the distance to the epicenter was ± 3700 km.